Relationship between higher education teachers’ affect and their psychological adjustment to online teaching during the COVID-19 pandemic: an application of latent profile analysis - Zou, Weixing; Ding, Xiangmei; Xie, Lingping; Wang, Hongli (PeerJ, 2021)
Background The COVID-19 outbreak has forced teachers to transition to online teaching, requiring them to adapt their courses and pedagogical methods to an online format rapidly without relevant training. This has presented a formidable challenge to higher education teachers. The present study uses a person-centered approach to identify heterogeneity among higher education teachers’ affective experiences and the relationship between this heterogeneity and their psychological adjustment to online teaching. Methods In total, 2,104 teachers in higher education institutions in Southern China were surveyed using the Positive and Negative Affect Schedule and the Psychological Adjustment to Online Teaching Scale (a measure developed for this study) between March 25 and March 31, 2020. The collected data were analyzed using latent profile analysis. Results Based on their affective experiences during online teaching immediately after the COVID-19 outbreak, higher education teachers were divided into three latent classes: the common, ambivalent, and positive types. Among them, the positive type accounted for the largest proportion (44.85%), while the ambivalent type accounted for the smallest proportion (23.93%). The rest was the common type, which accounted for 31.15%. Significant differences in psychological adjustment to online teaching were found between the three latent classes. Regarding positive psychological adjustment, teachers belonging to the ambivalent type had significantly lower scores than those belonging to the other two types. Further, the common type had a significantly lower score than the positive type. Regarding negative psychological adjustment, the ambivalent type had a significantly higher score than the other two types, and the common type had a significantly higher score than the positive type. Conclusion Based on a novel person-centered perspective, this study revealed the differences and complexity in higher education teachers’ affective experiences of online teaching immediately after the COVID-19 outbreak. The three different types of affective experiences (common, ambivalent, and positive) had a significant influence on psychological adjustment, with teachers belonging to the ambivalent type showing the worst psychological adjustment. This study provides a new perspective for the discussion of the relationship between teachers’ affective experiences and their psychological adjustment to online teaching.
Keywords: Positive affect; Negative affect; Psychological adjustment; Online teaching; Latent profile analysis; COVID-19 pandemic